Effects of Implementing the Discovery Learning Model on Students' Critical Thinking Skills in Fluid Material - Aulia, Mhd Reyfanza Aulia; Darvina, Yenni; Desnita, Desnita; Suherman, Dea Stivani (Universitas Negeri Padang, 2025)
Twenty first century education requires students to possess critical thinking skills as part of their core competencies. This study aims to determine the effect of the Discovery Learning model on improving students’ critical thinking skills in both affective and cognitive domains. The research employed a pre-experimental method with a one-group pretest-posttest design, and the sample was selected using a simple random sampling technique. The instruments used were observation sheets and tests designed to measure critical thinking skills in both domains. The results showed a significant improvement in students' affective and cognitive abilities after the implementation of the Discovery Learning model. In the affective domain, the average score increased from 67.50 to 83.33, with an N-Gain of 0.487 (moderate category) and an Effect Size of 1.174 (high impact). The cognitive domain showed improvement across four critical thinking indicators, with an average N-Gain of 0.660 (moderate) and an Effect Size of 5.633 (high). The hypothesis test result (th = 30.854 > tt = 2.045) indicating a significant influence of the Discovery Learning model on the development of students’ critical thinking skills. Thus, the implementation of the Discovery Learning model is proven effective in enhancing students' critical thinking skills in both affective and cognitive aspects.